An Interview with Elizabeth Povinelli: Geontopower, Biopolitics and the Anthropocene. (May 2017) - Povinelli, Elizabeth A.; Coleman, Mathew; Yusoff, Kathryn
This article is an interview with Elizabeth Povinelli, by Mathew Coleman and Kathryn Yusoff. It addresses Povinelli's approaches to 'geontologies' and 'geontopower', and the discussion encompasses an exploration of her ideas on biopolitics, her retheorization of power in the current conditions of late liberalism, and the situation of the inhuman within philosophical and anthropological economies. Povinelli describes a mode of power that she calls geontopower, which operates through the governance of Life and Nonlife. The interview is accompanied by a brief contextualizing introduction.